OUTCOMES OF BALLOON MITRAL VALVULOPLASTY IN PREGNANT WOMEN: A SINGLE-CENTER EXPERIENCE - Mirjamol M. Zufarov; Vadim M. Im; Sanjar K. Khamdamov; Mohima A. Abdullayeva (Central Asian Journal of Medicine, 2024)
Analysis of the results and evaluation of the effectiveness of balloon mitral valvuloplasty (BMV) using the Inoue technique was conducted in 32 pregnant patients with rheumatic mitral stenosis, aged between 21 and 39 years (mean age 29.8 ± 5.2 years). The gestational age ranged from 23 to 33 weeks (mean 26 ± 1.6 weeks). Four patients (12.5%) had restenosis of the mitral orifice following closed mitral commissurotomy. Initially, 29 patients (90.6%) presented with New York Heart Association (NYHA) Class II heart failure, and 3 patients (9.4%) had Class III heart failure. The indication for intervention was based on the clinical presentation and a mitral orifice area (MOA) of less than 1.5 cm². All pregnant patients successfully underwent BMV without any complications. According to echocardiographic data, the mitral orifice area immediately after BMV ranged from 1.6 to 2.4 cm². On average, the MOA increased from 1.0 ± 0.2 cm² to 2.1 ± 0.2 cm² (p<0.05). The trans-mitral gradient decreased from an average of 22.9 ± 4.6 mm Hg to 12.9 ± 5.0 mm Hg (p<0.05). All patients reported an improvement in their condition immediately after the successful BMV procedure in the catheterization laboratory. Subsequently, they delivered healthy children without any complications. Based on the obtained data, it is concluded that BMV using the Inoue technique under echocardiographic monitoring with minimal use of fluoroscopy is both feasible and highly effective in pregnant patients.